Analisis Sistem Dan Prosedur Penggajian Serta Pengupahan Dalam Meningkatkan Efektivitas Pengendalian Intern PT Maju Jang Jaya Lubuklinggau - Noorchamid Ustadi; Sardiyo Sardiyo; Arisky Andrinaldo; Vina Dharvika Rani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research uses descriptive qualitative research. In this study using primary and secondary data sources. The data collection technique used by the researcher is the technique of observation, interviews and documentation from PT. Forward Jang Jaya. Based on the analysis of the payroll and wage accounting system, it can be seen that 1) Functions related to the payroll and wage system at PT. Maju Jang Jaya has not fully carried out their duties properly because of the dual tasks carried out by the finance department / cashier, namely as a maker of payroll and salary lists as well as payment of salaries and wages, documents used in the payroll and remuneration system. PT. Maju Jang Jaya is good enough, but still not perfect because there is no salary envelope document. 2) Bookkeeping payroll system and wage system at PT. Maju Jang Jaya has done enough so that it can support the effectiveness of internal control. The network of procedures that make up the payroll and remuneration system has not been fully effective because employee absenteeism is not supervised by the payroll department, so that it can trigger the risk of absenteeism and the occurrence of errors or other fraudulent acts and the organization. structure of PT. Maju Jang Jaya is not good because it does not separate the function of the payroll maker from the payer of the salary. 3) The authorization system has not fully supported the elements of internal control related to payroll and wages because it has not shown evidence of the accountability of the authorities in it and the implementation of the payroll and wage system at PT. Maju Jang Jaya has not fully implemented healthy practices because employee absenteeism is not supervised by the payroll department.